The Influence of Socio-Economic Status, Parenting Style, and Self-Control on Children's Prosocial Behavior - Suryadi, Suryadi; Dhieni, Nurbiana; Edwita, Edwita (Islamic Guidance and Counseling Journal, 2025)
The development of prosocial behavior in early childhood is crucial as it shapes future character and social interactions. This study explores the influence of socio-economic status, parenting patterns, and self-control on children’s prosocial behavior based on the Pancasila student profile at PAUD institutions in Lampung Province. Employing an associative quantitative approach with path analysis, the study involved 400 group B students. Data was collected through questionnaires, with socio-economic and parenting sections completed by parents, and prosocial behavior assessed by teachers. The instrument was tested for validity and reliability empirically, with valid items further evaluated using Cronbach's Alpha. Analysis was conducted using descriptive and inferential techniques with SmartPLS version 4. The findings reveal: (1) socio-economic status significantly affects parenting patterns, (2) socio-economic status directly influences self-control, (3) socio-economic status positively impacts prosocial behavior, (4) parenting patterns influence self-control, (5) parenting patterns directly affect prosocial behavior, and (6) self-control significantly impacts prosocial behavior. The study concludes that socio-economic status, parenting patterns, and self-control positively and directly shape prosocial behavior in alignment with the Pancasila student profile. Additionally, the indirect effect of socio-economic status on prosocial behavior through parenting patterns was found to be even more significant. These findings highlight the importance of fostering a supportive socio-economic environment, effective parenting, and strong self-control to nurture prosocial behavior in early childhood, contributing to the development of children who embody the values of the Pancasila student profile.